CULTURE SHOCK COMMUNICATION MAHASISWA PENDIDIKAN BAHASA ARAB - Siti Maisaroh (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: Culture shock is a natural phenomena. It is actually the first step to build up our personality and cultural understanding so that we turn into a flexible and skilled person to socialize with other language of many different specification, such as culture, phonetic, morphologhy and sintax etc. culture shock communication is also experienced by new university student from Madura which they have to communicate by Arabic language for one year during stay in central Arabic corner that located to Syaichona Moh. Cholil University Bangkalan city. Most of them have sympthoms of culture shock in several phases. This is due to their emotional condition which hiy everyone when he/she enters new different language culture. People are accustomed to be shock if they find that their culture has been changed. In addition, people are more comfortable with their environment and they tend to be used to with this familiarity. This assists to reduce the shock since people know what they hope of the new environment and come to new environment, problem communication can be solved. Keywords: culture shock, communication, environment